Odnos fibrinogena i albumina povezuje sistemsku upalu sa osteoporotskim prelomima i pokazuje diskriminativne performanse zajedno sa PLR, NLR i MLR: Fibrinogen–Albumin Ratio and Inflammatory Markers in Osteoporotic Fractures - Fu, Youxin; Cao, Daigui; Liu, Zeyu; Liu, Zhiwei; Guo, Jianping; Zhou, Xu; Hao, Jie (Journal of Medical Biochemistry, 2026)
Background: Osteoporotic fracture (OPF) remains a major cause of disability in older adults. Laboratory-available composite indices integrating coagulation, inflammation, and nutritional status may facilitate risk stratification in patients with osteoporosis. Objective: To investigate the relationship between the fibrinogen-to-albumin ratio (FAR) and systemic inflammatory indices (platelet-to-lymphocyte ratio [PLR], neutrophil-to-lymphocyte ratio [NLR], and monocyte-to-lymphocyte ratio [MLR]) in osteoporosis, and to evaluate their discriminative value for identifying concurrent osteoporotic fractures. Methods: This retrospective study included 98 patients with osteoporosis admitted between January 2024 and May 2025, categorized into a fracture group (n=39) and a non-fracture group (n=59). FAR, PLR, NLR, and MLR were calculated from routine laboratory tests obtained within 24 h of admission. Group differences were assessed, Pearson correlation was used to examine associations between FAR and inflammatory indices, and logistic regression was performed to identify independent clinical/imaging correlates of fracture. Receiver operating characteristic (ROC) curves were constructed to evaluate discriminative performance. Results: FAR, PLR, NLR, and MLR were significantly higher in patients with osteoporosis complicated by fracture than in those without fracture (all P